MOTOR NERVE IMPAIRMENT IN DIABETIC PATIENTS WITH SYMMETRICAL DISTAL SENSORY POLYNEUROPATHY: A SINGLE NERVE FIBER CONDUCTION VELOCITY STUDY - SÜNTER, GÜLİN; ULUÇ, KAYIHAN; TANRIDAĞ, TÜLİN (WILEY, 2014)
Introduction: In this study we investigated the clinical utility of single fiber conduction velocity (SF-CV) testing in the evaluation of motor nerve function in diabetic patients with signs and symptoms of symmetrical distal sensory polyneuropathy (DSP). SF-CV findings were compared with conventional nerve conduction studies (NCS). Methods: Twenty-eight consecutive type 2 diabetic patients with clinically diagnosed DSP were studied. Results: SF-CV testing of the tibial nerve was abnormal in 16 (57.1%) patients. Twelve patients with normal conventional motor NCS had abnormal findings by tibial SF-CV. SF-CV testing of the tibial nerve was significantly superior to all other motor NCS. Conclusions: SF-CV testing of the tibial nerve often demonstrates motor nerve impairment in diabetic patients with sensory DSP when conventional NCS are normal. Muscle Nerve49: 84-89, 2014
Keywords: conventional nerve conduction study; diabetes mellitus; distal symmetrical sensory polyneuropathy; motor nerve impairment; single fiber conduction velocity; F-WAVE LATENCY; MEDIAL PLANTAR; DISTRIBUTIONS; NEUROPATHIES; MELLITUS